Pengaruh Media Pembelajaran Berbasis Audio Visual terhadap Hasil Belajar pada Materi Lambang Garuda Pancasila di MIN 1 Pontianak - Khomisah, Yuyun; Fathurrosi, Fathurrosi; Harriska, Harriska (YASIN, 2025)
The low learning outcomes of students in Civic Education (PPKn), particularly in the topic of the Garuda Pancasila symbol, form the background of this study. This condition is influenced by students’ limited understanding of abstract material and the lack of engaging learning media. The purpose of this study is to examine students’ learning outcomes before and after the use of audiovisual media and to analyze the extent of its effect on the learning outcomes of third-grade students at MIN 1 Pontianak. A quantitative approach with a quasi-experimental design using a control group pre-test–post-test was employed. The study population consisted of all third-grade students at MIN 1 Pontianak, with total sampling applied. Research instruments included multiple-choice objective tests, observation, and documentation, while data were analyzed using SPSS version 27. The results show that the control group’s average pre-test score of 64.54 increased to 74.09 in the post-test, categorized as moderate improvement. Meanwhile, the experimental group improved from an average pre-test score of 63.80 to a post-test score of 82.85. Effect size analysis using Cohen’s d produced a value of 1.230, categorized as high. The study concludes that audiovisual learning media have a significant and effective impact on improving students’ learning outcomes in the Garuda Pancasila topic.